Holiness on the move
1 online resource (xvi, 255 pages)
Keywords: "Holiness on the Move: Mobility and Space in Byzantine Hagiography, explores the literary, religious, and social functions of monastic mobility in Byzantine hagiography, touching on aspects of space, narrative, and identity. The ten chapters included in this volume highlight the multifaceted and rich nature of travel narratives, exploring topics such as authorship and audience, narrative structure and function, identity-making and practicalities of and discourse on travel. In terms of geographical span, the case studies cover Constantinople and its hinterland, Asia Minor, mainland Greece, Trebizond, the Balkans, and southern Italy, and range chronologically from the end of the sixth to the fourteenth century. The contributions offer novel insights and perspectives on the importance of mobility in the literary construction of holiness in the Byzantine world and the wider medieval Mediterranean, the spatial dimension of sacred mobility, and the ways in which mobility is employed in the narrative construction of hagiographical texts. As such, the volume joins the burgeoning research on sacred mobilities and will interest students and scholars of Byzantine and medieval literature, religion, and history, as well as a wider readership with an interest in the study of space and mobility"--